Al-Rahn in Malaysia and Indonesia: Legal History and Upcoming Trajectory - Muhammadi, Fauzan; Razif, Nor Fahimah Mohd; Rahim, Rahimin Affandi bin Abdul (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2021)
Abstract: This article examines the legal history of the application of Al-Rahn in two countries: Malaysia and Indonesia. Malaysia and Indonesia have similar roots in the implementation of Islamic law during the emergence of Islamic kingdoms in the Nusantara. However, these two countries developed different legal systems after colonialism: Britain colonized Malaysia and the Netherlands colonized Indonesia. These two phases, the Islamic kingdoms and the colonization of two European nations (Britain and the Netherlands), also influenced the historical development of the application of Al-Rahn to date. This study was conducted normatively with a comparative approach to legal history. This study’s qualitatively processed data are secondary data in statutory documents, books, and journal articles related to Al-Rahn. Comparatively, it was found that Al-Rahn was legally applied in these two countries during the development of the Islamic kingdoms, but then receded and even sank during colonialization. The influence of European law, whether Common Law or Civil Law, was so deeply rooted that it took a while to reach the stage where Al-Rahn was set into motion again. However, the practice of Al-Rahn, both in Malaysia and Indonesia, is yet to be accommodated under a single legal basis, rather, it is scattered in several different laws and regulations.Abstrak: Artikel ini mengkaji sejarah hukum penerapan Al-Rahn di dua negara, yaitu Malaysia dan Indonesia. Malaysia dan Indonesia memiliki akar penerapan hukum Islam yang sama pada masa berseminya kerajaan-kerajaan Islam di wilayah Nusantara. Namun demikian, kedua negara ini memiliki corak sistem hukum yang berbeda pasca kolonialisasi; Inggris menjajah Malaysia dan Belanda menjajah Indonesia. Dua fase tersebut, kerajaan Islam dan kolonialisasi dua Bangsa Eropa (Inggris dan Belanda), turut serta mempengaruhi perkembangan sejarah penerapan Al-Rahn sampai saat ini. Kajian ini dilakukan secara normatif dengan pendekatan komparasi sejarah hukum. Data yang diolah secara kualitatif dalam penelitian ini adalah data-data sekunder berupa dokumen perundang-undangan, buku, dan artikel jurnal berkaitan dengan Al-Rahn. Secara komparatif ditemukan bahwa Al-Rahn secara legal diterapkan di dua negara ini pada masa kerajaan Islam berkembang, namun kemudian surut dan bahkan tenggelam semasa kolonialisasi datang menjajah dua negara tetangga ini. Pengaruh hukum Eropa, baik Common Law atau English Law, sangat kuat sehingga membutuhkan waktu lama sampai tahap di mana Al-Rahn dipraktikkan kembali. Walaupun demikian, praktik Al-Rahn, baik Malaysia dan Indonesia, masih belum memiliki gantungan hukum yang tunggal, namun masih terpencar-pencar di beberapa perundangan dan peraturan.